Optimalisasi Pembangunan Desa Patoa Kecamatan Bulawa Kabupaten Bone Bolango Lewat Penyusunan Peta Geologi - Permana, Aang Panji; Zainuri, Ahmad; Nugrahi, Putri Inayah; Mahmud, Fitria; Kiwo, Anince; Lahay, Muamart Gimnastiar; Ruru, Susanti; Simbala, Susilo Bintang; Mbuinga, Ansyar; Masay, Muhammad Syawal Ardiansyah; Paputungan, Qurota Ayuni; Panai, Irdiansyah (Universitas Negeri Gorontalo, 2025)
Geological maps at the village level are compiled using primary and secondary data, which contain descriptions of geological conditions such as types and distribution of rocks, relationships between rocks, geological structures, and others. This map is made on a scale of 1:12,000. The village geological map functions as a reference in developing village potential, especially related to mineral resources, rocks, geotourism, engineering geology, environmental geology, and as a means of learning geoscience for local students. In addition, this map can also be used as a source of information regarding potential geological disaster threats, such as earthquakes, landslides, volcanoes, tsunamis, and liquefaction. The purpose of this community service activity is to compile a geological map of Patoa Village as supporting data for accelerating village development. The compilation process is carried out through literature studies, field orientation, and geological surveys. The final result is a geological map of Patoa Village containing rock units, geological structures, and stratigraphy of the area. Based on unofficial lithostratigraphic nomenclature, it consists of a Holocene reef limestone unit, a Pliocene-Pleistocene piroclastic breccia unit, and a Pliocene-Pleistocene tuff unit.